Contextual pastoral education for responsible citizenship in a complex South Africa - Plessis, Amanda L. Du (HTS teologiese studies, 2023)
Universities’ teaching and learning strategies aim to prepare students for life and the workplace by creating a culture of innovation to solve real-life problems, so that they can participate constructively in society and lead fulfilling professional and personal lives. In order to reach this goal, teaching and learning must have at least three paradigms, namely pedagogical, cognitive and pragmatic or instrumentalist. A pragmatic paradigm presupposes practical, experiential teaching and learning. This paper explores interactive means within the pragmatic paradigm that can be included in the pastoral modules of theology education. The epistemology is from a practical theological perspective.Contribution: The contribution of this article is that experiential role-play activities can have a positive impact in the pedagogy of pastoral care and counselling. The insight of this article links with the developmental goals for effective theological education in South Africa.